HUBUNGAN ANTARA USIA DAN PENURUNAN TROMBOSIT DENGAN PENYAKIT DEMAM BERDARAH DENGUE - Sigalingging, Jasminten; Apriyani, Erni; Selly, Selly (JURNAL KESEHATAN TERAPAN, 2021)
Background: Dengue Hemorrhagic Fever (DHF) is an infectious disease caused by 4 (four) dengue virus serotypes (DEN-1, DEN-2, DEN-3, DEN-4) and has clinical manifestations such as fever, headache. ,muscle ache and joints with leukopenia, lymphadenopathy, thrombocytopenia, bleeding and plasma seepage associated with hemoconcentration (increased hematocrit) or accumulation of fluid in the body cavity. Objective: To see the relationship between age and decreased platelets with dengue hemorrhagic fever. Method: This type of research is a cross sectional study design with sampling using accidental sampling obtained 82 respondents. Results: The results showed that there was a relationship between p-value for age 0.015, and there was no relationship between p-value for platelet reduction of 0.073 with the incidence of dengue disease. Suggestion: input looks for factors associated with the incidence of dengue hemorrhagic fever but with different variables. Keywords: Age, Decreased Platelets, Dengue Hemorrhagic Fever